Mechanistic intersections between migraine and major depressive disorder - Micah Johnson; Yassine Filali; Anjayooluwa Adegboyo; Maureen Eberle; Abigail Townsend; Yamam Hussien; Catherine Marcinkiewcz; Rainbo Hultman (The Journal of Headache and Pain)
Abstract It has long been recognized that there are comorbidities between migraine and psychiatric disorders, especially major depressive disorder (MDD). Often this relationship is attributed to the psychological risk of having an intermittent debilitating disorder that causes a great deal of suffering. However, as evidence mounts about the mechanisms underlying each disorder, mechanistic overlap is beginning to emerge that suggests some shared underlying etiology. These findings span biochemical, genetic, physiological, neuroanatomical, and environmental levels of analysis. Here we review evidence for shared biological mechanisms between migraine and MDD by first searching for mechanisms of each disorder separately across levels of analysis, with an emphasis on current and historic treatments for each disorder. Search terms included each disorder separately largely across NIMH Research Domain Criteria (RDoC) levels of analysis, adding “environment” to genes, molecules, cells, circuits, and physiology. In order to focus our efforts on shared underlying mechanisms, we included studies in preclinical models of these disorders. This review was written to highlight the emergent themes with the most mechanistic overlap between the two disorders across levels of analysis. We prioritized reporting of the findings with more mechanistic detail, which often comes from preclinical studies with carefully controlled variables and tests of causality. As such, this review is aimed at providing new insight by identifying features that are shared between these disorders, including those that have largely not been previously recognized. By emphasizing preclinical studies and mechanisms of underlying constructs relating these disorders, such as sensory gain and processing of emotional stimuli, we intend for this review to stimulate new areas of investigation at both clinical and preclinical levels of research.